Alat pendeteksi asap/gas berbasis Smartphone - Mudassir Mudassir; Syarifuddin Kasim (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The rapid development of science allowspractitioners to always continue to make innovation to overcome problems that often interfere their activities. The Community Partnership Program (PKM) aims to (1) increase the knowledge of vocational school teachers and students at SMK Darussalam and SMK Negeri 5 Gowa (partner) in making smartphone-based smoke detection software that monitors the entire the smoke/ gas in a house, building, or their school, (2) to improve the partner's skills in making and utilizing the Smartphone-based Smoke Detectors software, and (3) to improve the partner's skills in connecting the Smartphone-based Smoke Detectors to internet network through RouterTP-Link Modem to make it work. The method used in this workshop is lecturing, discussion, question and answer session and demonstration. The results of the implementation program show that (1) the partner's knowledge in terms of making Smartphone-based Smoke Detector software increased, (2) the partner's skills in making and utilizing Smartphone-based Smoke Detector improved, (3) the partner's is able to connect the detector to internet network so that it can be functioned, both at close range and remotely using a Smartphone.